ANALISIS STRATEGI BISNIS PENGGILINGAN PADI (Studi Kasus Rice Milling Unit Gapoktan Rukun Sejahtera Di Pekon Sukorejo Kecamatan Pardasuka Kabupaten Pringsewu) - Wildan Al Faris; Handayani, Sri; Noer, Irmayani; Irawati, Luluk (Program Studi Pengelolaan Agribisnis, 2025)
The Farmers’ Group Association (Gapoktan) Rukun Sejahtera received assistance from the local district government in the form of a Rice Milling Unit (RMU) machine to improve farmers’ welfare in the region. However, the RMU has not yet operated its business optimally. Based on pre-survey data (2025), rice sales at RMU Rukun Sejahtera reached a total production of 91.456 tons, whereas the sales target set for 2024 was 150 tons. This indicates that the sales target was not achieved. As competition in the rice milling industry becomes increasingly competitive, it is necessary to develop appropriate business strategies to ensure sustainability and growth. This study aims to analyze the internal and external factors of the business, determine the business unit’s position, formulate alternative strategies, and establish strategic priorities. The analytical techniques employed include SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis and QSPM (Quantitative Strategic Planning Matrix) to select the most effective strategies for implementation. The findings of this research identify six strength factors, five weaknesses, five opportunities, and five threats. The SWOT analysis generated three S-O strategies, two W-O strategies, two S-T strategies, and one W-T strategy. The QSPM results rank the strategic priorities as follows: first, “collaborating with farmers to secure rice supply” with a score of 6.78; second, “improving business management through mentoring programs” with a score of 6.60; and third, “creating own products to reach market segmentation” with a score of 6.56. The formulated strategies are expected to enable RMU Rukun Sejahtera to operate its business sustainably in the long term.